The Development of Pop-Up Book Learning Media to Enhance Students' Learning Interest - Agustina, Dina; Sunarto, Andang; Bahri, Husnul (Journal of Educational Sciences, 2025)
Teachers are encouraged to create innovative learning media that make learning more engaging and meaningful, especially in subjects that are often considered abstract, such as Islamic Religious Education. This study aims to develop a learning medium in the form of a pop-up book for the Islamic Religious Education and Character subject to enhance the learning interest of fourth-grade students at SDN 17 Kota Bengkulu. The research employs a Research and Development (R&D) method using the 4-D model (Define, Design, Develop, Disseminate). The data were obtained from both qualitative and quantitative sources. Qualitative data consisted of feedback from media experts, content experts, subject teachers, and students. Quantitative data were derived from validation assessments and student response questionnaires. The results showed that (1) the pop-up book media was categorized as highly valid, with validation scores from content experts (100%), media experts (100%), and subject teachers (96%); (2) the practicality of the media, based on student responses, reached 94%, indicating a very practical category; and (3) students' interest in learning using the media averaged 87%, showing that the pop-up book media effectively increases learning motivation.